Tinjauan Komparatif Bahasa Arab dan Bahasa Inggris Aforisme Al-Hikam: Analisis Sintaksis - Muhammad Yunus Anis (Badan Pengembangan dan Pembinaan Bahasa, 2022)
This article will investigate the Arabic language and English language based on Syntax analysis. In this case, syntax had been viewed as the arrangement between certain word and the other word, or with the other units of language which has the higher level than the word, such as: phrase, clause, and sentence. Generally speaking, this research will investigate the Arabic language based the four main theory in syntax (Liliane Haegeman, 1998), such as: (1) transitivity, (2) X-bar theory, (3) theta theory, and (4) case theory. This article will focus comprehensively in elaborating the data, both in Arabic language and English language, comparatively based on these four main theories. The material objects in this research was the units of language which had been collected from the book of Al-Hikam aphorism in trilingual edition (Arabic, Indonesia, and English). The observation method had been used for collecting the data, after that, the data will be analysed with two main steps, they are: distributional method and comparative method. Transitive verbs in al-Hikam's aphorisms show God's behavior. The transitivity of verbs in Arabic is determined by the noun that comes after the verb. Meanwhile, based on the study of X-Bar theory in Arabic phrases that appear in al-Hikam's aphorisms, it can be concluded that the internal structure of noun phrases, that FN = N + Adj and FN = N + N. Furthermore, in the theta theory analysis, it can be concluded that FN in the form of (N + Adj) can occupy the AGENT position and FN in the form of (N + N) can occupy the PATIENT argument to form a propositional unit. Based on the case theory study, it can be concluded that the NOMINATIVE case is in the subject who acts as the AGENT, and the ACCUSATIVE case is in the direct object that becomes the object of the sufferer or target, namely acting as the PATIENT. The result of this research can be the new model of Arabic and English language analysis based on the syntax theory.AbstrakArtikel ini akan mengkaji bahasa Arab dan bahasa Inggris ditinjau dari sudut pandang sintaksis. Dalam hal ini, sintaksis dipandang sebagai pengaturan hubungan antara kata dengan kata, atau dengan satuan yang lebih besar dalam bahasa. Secara garis besar kajian ini akan menginvestigasi bahasa Arab ditinjau dari kajian empat teori sintaksis (Haegeman, 1998), yaitu: (1) transitivity, (2) X-bar theory, (3) theta theory, dan (4) case theory. Adapun secara khusus, artikel ini akan mengelaborasi data bahasa Arab dan bahasa Inggris secara komparatif berlandaskan pada keempat teori tersebut. Objek material dalam kajian ini adalah satuan kebahasaan (units of language) yang ada dalam kitab aforisme al-Hikam versi tiga bahasa (Arab, Indonesia, dan Inggris). Penjaringan data dilakukan dengan cara observasi kemudian data dianalisis dengan menggunakan dua tahap, yaitu: metode distribusional dan metode padan. Verba transitif dalam aforisme al-Hikam menunjukkan perilaku ketuhanan tertentu. Ketransitifan verba dalam bahasa Arab ditentukan oleh nomina yang muncul setelah verba. Sementara itu, berlandaskan pada kajian X-Bar theory dalam frasa bahasa Arab yang muncul dalam aforisme al-Hikam dapat disimpulkan struktur internal frasa nomina, bahwa FN = N + Adj dan FN = N + N. Selanjutnya dalam analisis theta theory, dapat disimpulkan bahwa FN yang berupa (N + Adj) dapat menduduki posisi agent dan FN yang berupa (N + N) dapat menduduki argumen patient untuk membentuk sebuah satuan proposisi. Berlandaskan pada kajian case theory dapat disimpulkan bahwa kasus nominatif berada dalam subjek yang berperan sebagai agent, dan kasus akusatif berada dalam objek langsung yang menjadi penderita atau sasaran, yaitu berperan sebagai patient. Kontribusi pembahasan dari kajian ini diharapkan dapat memberikan wawasan baru dalam kajian bahasa Arab dan bahasa Inggris yang ada di Indonesia, khususnya terkait dengan kajian sintaksis (Arab: Ilmu-Naḥwu).